2019
DOI: 10.1186/s40494-019-0308-4
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the painterly technique beneath the surface of Vermeer’s Girl with a Pearl Earring using macro- and microscale imaging

Abstract: The initial steps that Johannes Vermeer took to create Girl with a Pearl Earring (c. 1665) are, partially or completely, hidden beneath the painted surface. Vermeer's painting technique involved applying underlayers that vary in colour and thickness, on top of which he applied the upper paint layer(s). To investigate the painting's genesis, the Girl was examined using non-invasive scientific imaging as part of the project The Girl in the Spotlight (2018). This was complemented by the re-examination of existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 13 publications
2
44
0
Order By: Relevance
“…If the underlayer is absorbing in the NIR, then the NIR reflectance should decrease, as is observed here. These results are in agreement with earlier findings about the underlayers beneath the headscarf: a black underpaint is present beneath the shadow part, and the left (lit) side was painted directly onto the grey ground, which contains carbon black [20]. While the RIS image cube is useful for determining the distribution of ultramarine, in this case it is harder to discern the distribution of lead white due to absorption from the dark underlayer and ground.…”
Section: Blue Part Of Headscarfsupporting
confidence: 91%
See 1 more Smart Citation
“…If the underlayer is absorbing in the NIR, then the NIR reflectance should decrease, as is observed here. These results are in agreement with earlier findings about the underlayers beneath the headscarf: a black underpaint is present beneath the shadow part, and the left (lit) side was painted directly onto the grey ground, which contains carbon black [20]. While the RIS image cube is useful for determining the distribution of ultramarine, in this case it is harder to discern the distribution of lead white due to absorption from the dark underlayer and ground.…”
Section: Blue Part Of Headscarfsupporting
confidence: 91%
“…New research from the 2018 Girl in the Spotlight project confirmed that an infrared-absorbing underlayer lies beneath the entire background [20]. Vandivere et al ; c False-colour spectral unmixing map displaying the distribution of fluorescence endmember spectra shown in e, including the 'red' endmember with 620 nm emission peak, the 'blue' endmember with 707 nm emission peak, and the 'green' endmember with a slowly decreasing emission intensity; d raw fluorescence emission spectra from the FIS data cube from which the endmember spectra (e) were calculated to make the map in c; e Endmembers used for spectral unmixing.…”
Section: Introductionmentioning
confidence: 99%
“…The brown-black layer observed in the samples FC5a, FC7a and FC9a by Kühn is an indication of Vermeer's practice of beginning his compositions in neutral dark tones, and has subsequently been observed in other studies on Vermeer paintings [9][10][11]. This layer is similar to the dark undermodelling present in the three samples taken for the present study.…”
Section: Discussionsupporting
confidence: 85%
“…In Girl with a Pearl Earring (c. 1665, Mauritshuis) ( Fig. 1a), Vermeer used ultramarine extensively in the Girl's headscarf, and mixed with other pigments in the shadows of her yellow jacket [6][7][8]. A trace amount of ultramarine was also found in the pink flesh paint.…”
Section: Introductionmentioning
confidence: 99%
“…MS-IRR was able to visualise the black carbon-containing underlayers. The extension towards longer wavelengths allows penetration beneath lead white-containing surface paint layers [7]. MA-XRF mapped the distribution of chemical elements in the paint layers of the headscarf, from which pigments could be inferred [13].…”
Section: Introductionmentioning
confidence: 99%